Pemanfaatan Limbah Rumah Tangga: Solusi Cerdas untuk Pupuk Organik Cair Berkualitas Cair di Desa Banteng Tersono Batang - Ahmad Rizal Fikri; Iqbal Imam Taufiq; Catelia Rifqi Lestari; Irma Juliana; Muhammad Azkiyak; Lathif Hanafir Rifqi (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
The amount of waste and residual materials produced by human enrichment increases every year along with the increasing population. Empowering household units in managing domestic organic waste has the potential to reduce organic waste, including food waste. In addition to disposing of household organic waste, it can also be used as raw material for making compost. The purpose of this community service activity is to demonstrate liquid organic fertilizer production techniques to the local community and increase public awareness of the benefits of household waste processing. This activity was attended by 20 people from household representatives in Banteng Village, Tersono District, Batang Regency. The demonstration service method implemented was considered effective in terms of the interest and level of innovation of the community in utilizing empty land as a follow-up to making liquid organic fertilizer independently.